Heat and cold therapy in sports - Rethinking mechanisms and clinical applications - Hotfiel, T.; Engelhardt, M.; Hammer, C.; Grim, C.; Freiwald, J. (Sports Orthopaedics and Traumatology, 2025)
Summary Injury and exercise during training and competition are associated with mechanical and metabolic stress. This results in a (patho-) physiological and immunological reaction that can have a physiological (increased endurance and performance) or pathophysiological effect (overuse, misload, misuse, injuries). In this context, heat and cold therapy are among the most traditional and established forms of physical therapy for supporting training-related adaptation reactions, optimizing regeneration, and treating sports injuries. Despite the frequency of its application, there are only a few empirically proven recommendations for its use in sports, depending on the indication and goal. This review article considers the physiological principles and clinical applications of heat and cold therapy in sports and provides information on how to use them for specific indications. Zusammenfassung Verletzungen sowie Trainings- und Wettkampfbelastungen bewirken mechanischen und metabolischen Stress. In Folge kommt es zu einer (patho-)physiologischen und immunologischen Reaktion, die physiologisch (Belastungs- und Leistungssteigerung) oder pathophysiologisch wirken kann (Über- und Fehlbelastungen, Verletzungen). In diesem Zusammenhang zählt die Wärme- und Kältetherapie zu den traditionsreichsten und etabliertesten physikalischen Therapieformen zur Unterstützung von trainingsbedingten Anpassungsreaktionen, zur optimierten Regeneration und zur Behandlung von Sportverletzungen. Trotz der Anwendungshäufigkeit von Wärme- und Kältetherapien existieren im Sport jedoch nur wenige empirisch gesicherte Empfehlungen zum indikations- und zielgerechten Einsatz. In der Übersichtsarbeit wird die Wärme- und Kältetherapie im Sport unter Berücksichtigung der physiologischen Grundlagen und klinischen Anwendungsfelder betrachtet sowie Hinweise zum indikationsgerechten Einsatz gegeben.